The Efforts to Build a Service-Oriented Licensing Legal System - A Sugirman (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
The service culture of the state civil apparatus often comes under scrutiny. Maladministration practices are the main cause. This research aims to analyse efforts to develop a service-oriented licensing legal system. To answer the issue, this research is conducted using normative legal research with two types of approaches, namely statutory approaches and conceptual approaches. Data was obtained through literature study and analysed using descriptive analysis technique. The results of the research show that efforts to develop a service-oriented licensing legal system requires a separate law that adopts the principles in providing services in the licensing sector. Thus, public services in the nature of goods are subject to the Public Service Act. Meanwhile, public services in the nature of licensing services are subject to separate laws relating to licensing